Recent advances in antibiotic resistance diagnosis using SERS: focus on the "Big 5" challenges. Issue 21 (26th September 2022) - Hassanain, Waleed A.; Johnson, Christopher L.; Faulds, Karen; Graham, Duncan; Keegan, Neil
Abstract : SERS for antibiotic resistance diagnosis. Abstract : Antibiotic resistant bacteria constitute a global health threat. It is essential for healthcare professionals to prescribe the correct dose of an effective antibiotic to mitigate the bacterial infection in a timely manner to improve the therapeutic outcomes to the patient and prevent the dissemination of antibiotic resistance. To achieve this, there is a need to implement a rapid and ultra-sensitive clinical diagnosis to identify resistant bacterial strains and monitor the effect of antibiotics. In this review, we highlight the use of surface enhanced Raman scattering (SERS) as a powerful diagnostic technique for bacterial detection and evaluation. Initially, this is viewed through a lens covering why SERS can surpass other traditional techniques for bacterial diagnosis. This is followed by different SERS substrates design, detection strategies that have been used for various bacterial biomarkers, how SERS can be combined with other diagnostic platforms to improve its performance towards the bacterial detection and the application of SERS for antibiotic resistance diagnosis. Finally, the recent progress in SERS detection methods in the last decade for the " Big 5 " antibiotic resistant challenges as demonstrators of public health major threats is reviewed, namely: Methicillin-resistant Staphylococcus aureus ( MRSA ), Carbapenem-resistant Enterobacteriaceae ( CRE )/ Extended-spectrum beta-lactamases ( ESBLs ), Mycobacterium tuberculosis ( TB ), Vancomycin-resistant Enterococcus ( VRE ) and Neisseria Gonorrhoea ( NG ). This review provides a comprehensive view of the current state of the art with regard to using SERS for assessing antibiotic resistance with a future outlook on where the field go head in the coming years.